Study on Clinico-Laboratory Profile of Children with Scrub Typhus - Jain, N; Jain, V (Journal of Nepal Paediatric Society, 2012)
Scrub typhus is an acute, febrile, infectious illness caused by Orientia (formerly Rickettsia) tsutsugamushi,an obligate intracellular gram-negative bacterium. Humans are accidental hosts in this zoonotic disease.The present retrospective study describes clinical profile of the children hospitalized in hospital with Scrub Typhus infection during period 2010-2011. 19 hospitalized children with clinical features suggestive of Rickettsial disease (fever, generalized rash) who tested ELISA positive for IgM against Scrub Typhus were included in the present study between the age of 1 years and 15 years. All children presented with fever (100%). 42.10% had lymphadenopathy, 47.36% had eschar and 57.89% patients had cough. 26.31, 21.05%, 10.52%, had hepatomegaly, pain abdomen, and respiratory distress and gastrointestinal bleed respectively. All of the children were investigated and treated with as per protocol. None of them died. We think that Rickettsial infection is not quite common in this region but study showed that it is not an uncommon entity and thus, high degree of suspicion, knowledge of geographical distribution and clinical features of Rickettsial disease helps in its early diagnosis and treatment. J Nepal Paediatr Soc 2012;32(2):187-192 doi: http://dx.doi.org/10.3126/jnps.v32i2.5683